The united geodetic vertical network of Latvia and Lithuania - Aleksejenko, Ivars; Sakne, Janis; Kalinka, Maris; Reiniks, Martins; Kalantaite, Ausra; Krikstaponis, Boleslovas; Parseliunas, Eimuntas Kazimieras; Petroskevicius, Petras; Viskontas, Povilas (Geodesy and Cartography, 2012)
A unified and continuous national vertical network is the back-bone for geodesy, cartography, civil engineering and global positioning. International institutions are working to reach homogenous and unified vertical datum all around the globe. Levelling evaluation on the border between Latvia and Lithuania is of particular interest. Connection between vertical networks is made in three places, so connecting lines construct the two first order levelling loops. A joined loop adjustment produces a good basis for analysis and evaluation of height connection between Latvia and Lithuania not only as neighbouring countries but also as parties to the EVRS.